ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SEBELUM DAN SETELAH PEMILIHAN PRESIDEN SECARA LANGSUNG 9 JULI 2014 (STUDI KASUS PADA SAHAM LQ-45) - Rizkia Nur Hutami; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2015)
A political conditions, such as the presidential election (election), legislative elections (pileg), changes of government, the announcement of the cabinet ministers, political unrest, and other events greatly affect the price and trading volume in the stock exchange due to political events closely related to the stability of the economy the country. Political events to be tested contains information on the activities of the stock exchange is the presidential election event on July 9, 2014. The purpose of this study was to analyze the differences in the average abnormal return and trading volume activity in the LQ-45 before and after the presidential election July 9 2014. The population of this study are all financial data included in the LQ-45 in IDX. Sampling method used in this research is purposive sampling method. The sample used in this study were 45 financial data included in the LQ-45 on the Stock Exchange during the observation period (2 July to July 16, 2014). The data used are secondary data from BEI. The analysis technique used is event study. Based on a statistical test of the average abnormal stock returns during the event period, it was found that there was no difference in the average abnormal return before and after the presidential elections on July 9, 2014. Based on the test results depending average trading volume activity before and after the event IDX suspend, indicates that there are statistically significant differences in the average trading volume activity before and after the presidential election July 9, 2014.